2020
DOI: 10.18332/ejm/114886
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and perceptions of Nigerian parents towards human papilloma virus (HPV) vaccines

Abstract: INTRODUCTION Human papilloma virus (HPV) is a renowned cause of cervical cancer, which has resulted in high mortality of individuals. Cervical cancer could be reduced by screening and HPV vaccination. This study investigated knowledge, attitudes and perceptions of parents towards HPV vaccines in Ibadan, South-West L.G.A, Oyo State, Nigeria. METHODS A cross-sectional descriptive design was used with a multi-stage sampling technique to select 186 parents from Ibadan South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…These sources include friends, parents, and health workers. However, this finding strengthens some Nigerian studies that reported that friends, health workers and parents can be a source of information on HPV and HPV vaccine 41,[59][60][61][62] .…”
Section: Discussionsupporting
confidence: 83%
“…These sources include friends, parents, and health workers. However, this finding strengthens some Nigerian studies that reported that friends, health workers and parents can be a source of information on HPV and HPV vaccine 41,[59][60][61][62] .…”
Section: Discussionsupporting
confidence: 83%
“…These control strategies against cervical cancer are enhanced by early detection of HPV and the treatment of pre-cancerous lesions. The HPV vaccine has also been recommended by WHO as the fundamental approach for the prevention of cervical cancer, and should ideally be administered preceding first sexual contact ( 11 ). Although the vaccines have been approved for administration in Nigeria since 2009, it is mostly accessible to privileged individuals that can afford the cost ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The HPV vaccine has also been recommended by WHO as the fundamental approach for the prevention of cervical cancer, and should ideally be administered preceding first sexual contact ( 11 ). Although the vaccines have been approved for administration in Nigeria since 2009, it is mostly accessible to privileged individuals that can afford the cost ( 11 ). This contributed to the major challenges limiting HPV vaccination exercise in Sub-Saharan Africa which is the non-release of funds by government agencies to sponsor free vaccination and the inability of low-earners to self-sponsor ( 12 - 14 ).…”
Section: Introductionmentioning
confidence: 99%